PENGARUH SIZE, LEVERAGE, PROFITABILITY, INVENTORY INTENSITY DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - STEFFI EFATA WIJAYA; MEIRISKA FEBRIANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to analyze and obtain empirical evidence of the effect of size, leverage, profitability, inventory intensity, and corporate governance to tax management. This research uses effective tax rate as an indicator to measure tax management. The population in this research is 136 manufacture companies that listed in Indonesian Stock Exchange from 2013 to 2015. Based on criteria, 62 manufacturing companies have obtained. The statistical method used in this research is multiple regression analysis. The result show that profitability has negative effect to tax management. Independent commissioner as an indicator of corporate governance has positive effect to tax management. Another result showed that size, leverage, and inventory intensity have no influence to tax management.